Fabrication, characterization and applications of cyclosiloxane based hybrid resin and nanocomposites thereof - Song, Yujie (2017)
The development of high-performance polymers/composites/nanocomposites has been one of main concerns nowadays, especially considering the consumption of finite resources. Silicone, which can be made from sands, has been widely used as high-performance polymer since applications in World War Ⅱ. In order to push the limit of silicones, cyclosiloxane polymer was developed to improve the thermal stability. However, lack of knowledge on cyclosiloxane polymer has provided little insight on structure-properties relationship.